Dampak pada Pernikahan Dini di Indonesia : Survei Demografi dan Kesehatan Indonesia 2017 - Dwi Rahmadini; Mondastri Korib Sudaryo (Universitas Ngudi Waluyo, 2021)
Indonesia is among the countries with the percentage of early marriages in the world, in 37th place. While in ASEAN, Indonesia submitted first place. Early marriage to a woman will have a negative impact because the growth of body organs, especially the reproductive organs are not ready for the process of pregnancy or birth so that it is categorized as a high risk for both pregnant women and fetuses in terms of health, psychological, and growth and development of children born. A cross-sectional study, subjects were the group of age 15-49 years who were followed by the interviews and had complete data. Data used was drawn from 2017 Indonesian Demographic Health Survey (IDHS). Logistic regression model was used for analysis. only 26.6% of the respondents had married before 18 years old. As compared to respondent high fertility (>2 child), all respondents with low fertility (<=2 child) were significantly about 1.19 times,Â POR values indicate that women who get married early are 1.19 times higher risk to have >2 child (a-POR=1.19; 95% CI:1.16-1.23). As compared to respondent who use contraception, POR values indicate that women who get married are 1.10 times higher risk to use contraception (a-POR=1.10; 95% CI:1.05-1.13). Respondents who living with high wealth index, POR values indicate that women who get early marriage were about 1.10 times higher risk with low wealth index (a-POR=1.13; 95% CI :1.11 â€“ 1.16).